2020
DOI: 10.1002/chem.202003042
|View full text |Cite
|
Sign up to set email alerts
|

meso‐ and β‐Pyrrole‐Linked Chlorin‐Bacteriochlorin Dyads for Promoting Far‐Red FRET and Singlet Oxygen Production

Abstract: As eries of chlorin-bacteriochlorin dyads (derived from naturallyo ccurring chlorophyll-a and bacteriochlorophyll-a), covalently connected either through the meso-aryl or b-pyrrolep osition (position-3) via an ester linkageh ave been synthesized and characterized as an ew class of far-red emittingf luorescence resonance energy transfer (FRET) imaging, and heavy atom-lacking singlet oxygen-producing agents.F rom systematic absorption, fluorescence, electrochemical, and computational studies, the role of chlorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…Such analysis yielded τ h values of 1.05×10 11 s −1 , 0.89×10 11 s −1 and 0.12×10 11 s −1 (error=±10 %), respectively, for 2 , 4 and 6 . The magnitude of these τ h values are in good agreement with earlier reported rate constants of energy transfer ( k ENT ) values in Chl−BChl dyads connected by a biphenyl spacer, [14] indicating occurrence of efficient excitation transfer in the present dimers.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Such analysis yielded τ h values of 1.05×10 11 s −1 , 0.89×10 11 s −1 and 0.12×10 11 s −1 (error=±10 %), respectively, for 2 , 4 and 6 . The magnitude of these τ h values are in good agreement with earlier reported rate constants of energy transfer ( k ENT ) values in Chl−BChl dyads connected by a biphenyl spacer, [14] indicating occurrence of efficient excitation transfer in the present dimers.…”
Section: Resultssupporting
confidence: 91%
“…With this goal in mind, the dimers were investigated using both femto‐ (fs‐TA) and nanosecond transient absorption (ns‐TA) spectroscopic techniques. The fs‐TA and ns‐TA characterization of monomeric chlorin and bacteriochlorin, used as control in the present study, is reported by us earlier [14] …”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations